2006
DOI: 10.1663/0013-0001(2006)60[205:pcoses]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Phenetic Comparison of Seven Echinacea Species Based on Immunomodulatory Characteristics

Abstract: The purpose of the present investigation was to compare similarities and differences in immune response among Echinacea species, which are commonly used to treat upper respiratory infections. The investigation involved two components: acquisition of immunomodulatory data reported here for the first time, and combined phenetic analysis of these data along with previous reports. Experimental data were obtained by stimulating human PBMC in vitro with extracts from Echinacea spp. and assaying production of three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…He hypothesized that the other species involved in the parentage of E. pallida was E. sanguinea ; the two “atypical” accessions are located on our dendrogram closer to E. sanguinea than to E. simulata . Support for a close biochemical relationship between E. pallida and E. sanguinea was reported recently by Senchina et al [26], who conducted a phenetic analysis of the immunomodulatory characteristics of seven Echinacea taxa. Binns et al [13] treated both E. simulata and E. sanguinea as varieties of E. pallida .…”
Section: Resultsmentioning
confidence: 53%
“…He hypothesized that the other species involved in the parentage of E. pallida was E. sanguinea ; the two “atypical” accessions are located on our dendrogram closer to E. sanguinea than to E. simulata . Support for a close biochemical relationship between E. pallida and E. sanguinea was reported recently by Senchina et al [26], who conducted a phenetic analysis of the immunomodulatory characteristics of seven Echinacea taxa. Binns et al [13] treated both E. simulata and E. sanguinea as varieties of E. pallida .…”
Section: Resultsmentioning
confidence: 53%
“…Other investigative teams as well as our own have shown that E. angustifolia , E. pallida , and E. purpurea differ in both activity and/or phytochemical composition [13, 1619, 21, 2632]. In a previous phenetic analysis [22], we established that Echinacea tennesseensis appears to exhibit in vitro immunomodulatory characteristics more similar to E. purpurea than to E. angustifolia or E. pallida . Results presented in this paper are consistent with previous findings and provide further support for that analysis.…”
Section: Discussionmentioning
confidence: 64%
“…Generalizing from studies reviewed in the Introduction [1922], in in vitro studies using human PBMCs, E. tennesseensis root tincture has been reported to increase IL-1β, decrease or have no effect on IL-2, increase or have no effect on IL-10, increase or have no effect on TNF, and increase or have no effect on PBMC proliferation. Comparisons between these studies should be made with the understanding that the studies differed in extraction processes, laboratory culture procedures, participant characteristics, and sample sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kindscher [17] [24]) ; -effet sur l'interféron ; -effet sur la transformation lymphoblastique (activation des lymphocytes T) ; -effet sur la microphagocytose ; -induction des interleukines IL-1 bêta TNF-alpha [25] ; -un léger effet bactériostatique, antiviral et antifongique ; -une réduction de l'inflammation dans les affections articulaires et les affections cutanées ; -un effet cortisone-like [18]. En externe -stimulation de régénération tissulaire dans les plaies ; -inhibition de l'hyaluronidase bactérienne.…”
Section: Echinacea Pallidaunclassified